Autographs in the rain - Jardine, Quintin, 1945- (Headline, 2002)
As Bob Skinner takes an evening stroll with a gorgeous filmstar on his arm, surely the worst of his worries is that back at Headquarters, an ambitious new colleague is scheming to enlarge his territory at Skinner's expense. But when a frightening shot-gun attack sends Skinner and his old flame Louise Bankier diving for cover, it seems danger has zeroed in on him once again. Returning to Scotland to shoot her latest film, Louise is one of Scotland's most popular exports. But it seems she has a stalker; someone who is clearly determined to scare her. For Skinner, tracking down her tormentor isn't just business - it's now very personal indeed. The Detective Chief Constable, however, is about to find out that nothing is quite what it seems..